Restorative Justice and Child Protection in Sharia Law: A Maṣlaḥah-Based Analysis from Langsa Sharia Court: Keadilan Restoratif dan Perlindungan Anak dalam Hukum Syariah: Analisis Berbasis Maṣlaḥah dari Mahkamah Syar’iyyah Langsa - Muhammad Rusdi bin Muhammaddiah; Safitri, Rahmad (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2025)
This study examines the phenomenon of the dominance of imprisonment sentences perpetrators of child rape cases in the Langsa Sharia Court in the period 2022-2024, which differs from the general characteristics of Islamic law that implements caning punishment. The urgency of this research lies in analyzing the judicial panel's fundamental considerations when choosing imprisonment over caning, as well as examining the perspectives of benefit (maṣlaḥah) and the best interests of child victims. The research employs empirical legal methods with a qualitative approach, utilizing in-depth interviews with Judges of the Sharia Court of Langsa and library data analysis. The findings indicate that judges tend to impose prison sentences as they are deemed more effective in ensuring children's development without prolonged trauma, and better guarantee the maṣlaḥah and best interests of the child victims' future. The preference for imprisonment is based on comprehensive considerations of trauma recovery and protection of children's interests.